Influence of Nursing professionals in choosing the type of delivery (Research, Society and Development, 2023)
Introduction: This study aims to analyze the role and influence of nursing in choosing the type of delivery in pregnant women during prenatal care. Methodology: This is an exploratory and descriptive study with a qualitative approach. The research subjects were 10 pregnant women and 10 puerperal women, over 18 years old, from the Basic Health Unit of a municipality in the interior of the state of Rio Grande do Sul. All responded to the semi-structured interview sent through the Google Forms platform from March to May 2023. Results: The age of the participants ranged from 18 to 50 years old. In addition, the number of cesarean sections was high, of the 10 puerperal women interviewed, 09 opted for cesarean delivery. The responses were grouped into 03 categories referring to pregnant and puerperal women: “Normal delivery”, “Cesarean delivery” and “Pharmacological and non-pharmacological methods of pain relief”. Final considerations: In an attempt to clarify pregnant women about the benefits of normal delivery, and reduce the high rates of cesarean sections prevalent throughout Brazil, nursing professionals play an increasingly important role in influencing the choice of type of delivery as they participate actively from all prenatal care. These provide information about the type of delivery, the benefits and particularities of each one. And the importance of information about the use of non-pharmacological pain relief methods.